(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Recently, the development of science is rapidly developing. This opens the way for the formation of new branches of many scientific fields. In particular, the fields of semiotics and pragmatics in linguistics are considered to be one of such budding directions. In this article, it is recognized that the fields of semiotics and pragmatics are considered to be the main factors in the formation of speech competence, and technologies for their correct and effective use in the process of communication have been developed. Especially in the current development of linguistics, knowing how to effectively use semiotic-pragmatic factors arising from the structure of anthropocentric direction in the development of speech competence ensures that this issue has a deeper position. Because the human factor and the theory of knowledge (epistemology) are essential in the speech process. These two are the literal owner and content of the speech. As a result of this linguistic research, the history of the origin of the factors of semiotics and pragmatics in the formation of speech competence, their components, and the scientific views of several scientists who contributed to the formation of these factors as a science are presented. Also, the necessary sources are shown about pragmalinguistics, which is the modern interpretation of the field of pragmatics, which is one of the elements of the science of semiotics in linguistics, and its strategies in the speech process.